2020
DOI: 10.1002/essoar.10504535.1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Eddies connect the tropical Atlantic Ocean and the Gulf of Mexico

Abstract: The Gulf of Mexico (GoM) is a semi-enclosed sea connecting the Caribbean Sea and the Atlantic Ocean through the Yucatan Channel and the Straits of Florida, respectively. The Loop Current (LC) is the most prominent physical feature in the GoM. It has a significant influence on various processes in the GoM, such as dispersal of spilled oil (e.g.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 19 publications
1
11
1
Order By: Relevance
“…On the Atlantic side of the Lesser Antilles, the flow is dominated by anticyclonic North Brazil Current (NBC) rings that collide with this island arc. In contrast to previous studies (Huang et al., 2021; van Westen et al., 2018), who based their analysis on the propagation of sea level anomalies, we concluded that Caribbean anticyclones are not remnants of NBC rings and that the bulk of their vorticity is locally generated near the island arc. Our model results indicate that the vertical structure of these anticyclonic eddies is diverse.…”
Section: Summary Discussion and Conclusioncontrasting
confidence: 99%
“…On the Atlantic side of the Lesser Antilles, the flow is dominated by anticyclonic North Brazil Current (NBC) rings that collide with this island arc. In contrast to previous studies (Huang et al., 2021; van Westen et al., 2018), who based their analysis on the propagation of sea level anomalies, we concluded that Caribbean anticyclones are not remnants of NBC rings and that the bulk of their vorticity is locally generated near the island arc. Our model results indicate that the vertical structure of these anticyclonic eddies is diverse.…”
Section: Summary Discussion and Conclusioncontrasting
confidence: 99%
“…Some fluid is indeed seen to penetrate into the Caribbean Sea, consistent with direct measurements of biogeochemical tracers (E. M. Johns et al., 2014). But this is accompanied by substantial filamentation, even southeastward, more consistent with the observed resistance of drifters and floats to bypass the Lesser Antilles Fratantoni and Richardson (2004) than with NBCRs connecting the tropical Atlantic with the Caribbean Sea (Huang et al., 2021).…”
Section: Resultssupporting
confidence: 54%
“…Here we question Huang et al. (2021) results based on theoretical arguments, specialized SSH data analysis, and observations by Fratantoni and Richardson (2004) of satellite‐tracked surface drifters and submerged floats, which show that they hardly traverse the Lesser Antilles. The main issue with the analysis by Huang et al.…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…As this study started, individual satellite SSS is capable of resolving the upper register of the mesoscale spectrum (spatial scale of 50–500 km and temporal scale of 10–100 days) (e.g., Hasson et al., 2019; Huang et al., 2021; Kolodziejczyk et al., 2021; Lin et al., 2019; Melnichenko et al., 2021; Olivier et al., 2020). These scales play an important role in the mixing and exchanges of water masses close to fronts, as a result of ocean circulation and atmospheric fluxes.…”
Section: Introductionmentioning
confidence: 99%